Mineralogical-chemical Alteration and Origin of Ignimbritic Stones Used in the Old Cathedral of Nostra Signora di Castro (Sardinia, Italy) - Columbu, Stefano (2019)
The pyroclastic rocks belonging to the Late Eocene-Miocene volcanic activity that occurred in Sardinia between 38 and 15 Ma ago were widely used as construction materials in several Romanesque churches of the easternmost Logudoro area, as well as in large parts of the Sardinia territory. In this work, the ancient Cathedral of Nostra Signora di Castro (twelfth century) was taken as a representative case study. There is no historical or archaeological evidence of ancient quarries. Based on the geochemical, petrographic, and volcanological data on several samples from an extensive field area (approximately 150km2), a geographical zoning of the volcanics has been recognised. In the Oschiri sector, there are three different sub-zones, which can be identified with different volcanic rocks: less fractionated rocks (Differentation Index ∼70–78); intermediately fractionated rocks (D.I. ∼76– 79); and more fractionated rocks (D.I. ∼77–82). To identify the origin of the ignimbrite rocks of the Church of Nostra Signora di Castro, two statistical methods were used: stepwise linear discriminant and canonical analysis. Moreover, to define the geochemical transformation processes induced by the alteration, a comparative study of concentrations of major and trace elements measured by XRF and SEM-EDX analyses on the surface portion and the innermost areas of the stone was made.